(untitled) (PerCursos, 2024)
Traditionally, the field of Brazilian Social Thought has canonized the interpretations of Brazil developed by white cis heterosexual men from the middle and upper classes, while neglecting and/or silencing the interpretations developed by black, indigenous, (trans) feminist and peripheral intellectualities. Therefore, this article rescues the contributions of black travestis and women and their respective interpretations of Brazil. For that, Lélia Gonzalez (1st generation), Cida Bento and Sueli Carneiro (2nd generation) and Megg Rayara Gomes de Oliveira (3rd generation) were elected to discuss the convergences and specificities of their (Trans) Black Feminisms that differentiate them from “classic” theorists. Thus, the debate focused on 3 main points: 1) the intersectional interpretation of Brazil with a focus on the inequalities and violence that racism, sexism and homotransphobia cause in the annihilation of human-dignity and citizenship of the black population; 2) the theoretical dialogues with other black intellectuals; and 3) the consideration of the resistances of the black population, both in theoretical terms and in their own practices, without separating intellectuality and militancy. It is concluded that such interpretations expose the contradictions and denials of official Brazil, and it is essential to consider the intellectuality of black travestis and women, as well as their respective contributions to Brazilian Social Thought, (Trans) Feminist Thought and Black Brazilian Social Thought as a way of complexifying understandings of what Brazil is.